Rozwój glottodydaktyki a kształcenie nauczycieli języków obcych - Komorowska, Hanna (Postscriptum Polonistyczne, 2020)
The article presents the results of the latest research in glottodidactics that can be used while planning and organizing professional training for foreign language teachers. It raises questions that have not been fully discussed yet and presents expectations about teachers’ abilities as well as training needs of teachers working in Poland and abroad. The author of the article analyses a development of foreign language teachers training in Poland over past twentyfive years pointing out its strengths and weaknesses. The author presents the conclusions that could improve teacher education and meet specific needs of foreign language teachers.